Compositions and methods for dry anode films containing silicon
By using a non-solvent dry process and a variety of dry adhesives in the energy storage device, combining graphite and silicon with different particle sizes, a high energy density and self-supported dry electrode film is produced, which solves the problems of insufficient performance of the existing electrode film and the limitations of manufacturing methods.
Patent Information
- Application Number
- JP2020554305
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-05-02
- Filing Date
- 2019-04-30
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2039-04-30
AI Technical Summary
The electrode films of existing energy storage devices are insufficient in practical applications, and traditional solvent-free manufacturing methods have limitations on the components of the electrode film, which affects performance improvement.
A dry electrode film with high silicon content is produced by a non-solvent dry process. By combining graphite with silicon with different particle sizes, a variety of dry adhesives (such as sodium hydroxymethylcellulose, polyethylene oxide, polyacrylic acid, polyvinylidene fluoride, etc.) are used as adhesives to form a self-supported dry electrode film.
It achieves high energy density and good mechanical properties, improves electrochemical charging and discharging capabilities, and is suitable for industrial processing.
Smart Images

Figure 0007666927000007 
Figure 0007666927000008 
Figure 0007666927000009
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 666,037, entitled "Compositions and Methods for Dry Anode Films Comprising Silicon," filed May 2, 2018, the entire disclosure of which is incorporated herein by reference.
[0002] The present invention relates to energy storage devices, and in particular to materials and methods for dry electrode films that include silicon-based active materials. [Background technology]
[0003] Electrical energy storage cells are widely used to power electronic, electromechanical, electrochemical, and other useful devices. Such cells include batteries, such as primary chemical cells and secondary (rechargeable) cells, fuel cells, and various types of capacitors, including ultracapacitors. Increasing the operating power and energy of energy storage devices, including capacitors and batteries, is desirable to enhance energy storage performance, increase power capabilities, and broaden practical use cases. Summary of the Invention [Problem to be solved by the invention]
[0004] Energy storage devices including electrode films that combine complementary attributes can improve the performance of energy storage devices in practical applications. Furthermore, existing dry and solvent-free manufacturing methods can impose practical limitations on the composition of electrodes. Therefore, new electrode film formulations, and their manufacturing methods, can expand the possibilities of electrode film formulations and, as a result, improve performance. [Means for solving the problem]
[0005] For purposes of summarizing the invention and its advantages achieved over the prior art, certain objects of the invention and its advantages are described herein. Not all such objects or advantages may be achieved in a particular embodiment of the invention. Thus, for example, one skilled in the art will recognize that the invention can be embodied or practiced in a manner that achieves or optimizes one or a group of advantages taught herein without necessarily achieving other objects or advantages taught or suggested herein.
[0006] One embodiment is a silicon-based lithium battery anode that includes two different graphite particle sizes and is fabricated by a non-solvent-based dry process. In the anode, the primary graphite is, on average (i.e., D 50 ) may have a particle size of about 20-30 μm, and the secondary graphite may have an average particle size of about 4-7 μm. The silicon component of the anode may include pure silicon, silicon oxide, prelithiated silicon, and silicon-carbon composites. In one embodiment, the silicon component comprises about 10% to 30% by weight of the total weight of the electrode formulation. The dry binder in the anode may include carboxymethyl cellulose, polyethylene oxide, polyacrylic acid, polyvinylidene fluoride, polytetrafluoroethylene, and combinations thereof. In one embodiment, the dry binder comprises about 4% to 10% by weight of the total weight of the anode formulation.
[0007] In a first aspect, a self-supporting dry anode film comprising a silicon active material is provided.
[0008] In a second aspect, a dry electrode film for an energy storage device is provided. The dry electrode film includes a dry active material including a Group 14 active material and a graphite active material, and a dry binder such that the dry electrode film is self-supporting.
[0009] In a third aspect, a method of manufacturing a dry electrode film for an energy storage device is provided, the method includes mixing a dry Group 14 active material with a dry graphite material to form a dry active material mixture, mixing the dry active material mixture with a dry binder to form a dry electrode film mixture, and calendaring the dry electrode film mixture to form a free-standing dry electrode film.
[0010] All of these embodiments are intended to be within the scope of the invention disclosed herein. These and other embodiments of the invention will become readily apparent to those of ordinary skill in the art from the following detailed description of the preferred embodiments, taken in conjunction with the accompanying drawings, although the invention is not limited to any particular preferred embodiment disclosed. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 illustrates an embodiment of an energy storage device including a silicon-based electrode film. [Diagram 2] FIG. 2 illustrates a method for fabricating a self-supporting anode electrode film comprising a Group 14 active material and one or more graphitic materials. [Diagram 3] FIG. 3 provides a bar graph comparison comparing the measured electrochemical charge capacity of embodiments of silicon / graphite composite dry anode electrode films according to Example 1 with the theoretical capacity calculated for each film. [Figure 4A] FIG. 4A is a bar graph showing the electrochemical charge and discharge capacities for the surface-modified artificial graphite / 10 wt. % Si (“AG”) and natural graphite / 10 wt. % Si (“NG”) composite anode electrode half-cell embodiments according to Example 2. [Figure 4B] FIG. 4B is a bar graph showing the coulombic efficiency. [Figure 4C] FIG. 4C is a bar graph showing energy density. [Figure 5A]5A-5C compare a graphite dry electrode ("0 wt % Si") with two embodiments of a silicon / graphite dry electrode containing 5 wt % silicon ("5 wt % Si") and 10 wt % silicon ("10 wt % Si") according to Example 3, and FIG. 5A is a bar graph showing the electrochemical charge and discharge capacities. [Figure 5B] FIG. 5B is a bar graph showing the coulombic efficiency. [Figure 5C] FIG. 5C is a bar graph showing electrode energy density. [Figure 6A] 6A-6C are diagrams illustrating the Si / PG / SG composite dry electrode half-cells containing 10 wt. % Si for formulations 2, 3, and 4 in Table 1 according to Example 4, and FIG. 6A is a bar graph showing the electrochemical charge and discharge capacities. [Figure 6B] FIG. 6B is a bar graph showing the coulombic efficiency. [Figure 6C] FIG. 6C is a bar graph showing electrode energy density. [Figure 7A] 7A-7C provide bar and line graphs for an embodiment of a SiC / PG / SG composite dry electrode half-cell according to Formulation 1 with 15 wt % silicon at various PG:SG mass ratios in accordance with Example 5, with FIG. 7A showing the electrochemical charge and discharge capacity. [Figure 7B] FIG. 7B shows the coulombic efficiency. [Figure 7C] FIG. 7C shows the electrode energy density. [Figure 8A] 8A-8C are bar and line graphs for an embodiment of a PG(AG) / SG(AG) composite dry electrode half-cell comprising silicon, silicon / graphene (SiC) and silicon oxide (SiO) according to Example 6, with FIG. 8A showing the electrochemical charge and discharge capacity. [Figure 8B] FIG. 8B shows the coulombic efficiency. [Figure 8C] FIG. 8C shows the electrode energy density. [Figure 9]FIG. 9 shows the ultimate tensile strength of embodiments of free-standing dry electrode films with various anode active materials according to Example 7. [Figure 10A] 10A-10C are bar graphs and line graphs of four embodiments of the SiO / PG / SG composite dry electrode film containing 10 wt% silicon active material as half cells using the electrolyte formulations listed in Table 4 according to Example 8, and FIG. 10A shows the charge capacity and discharge capacity. [Figure 10B] FIG. 10B shows the coulombic efficiency. [Figure 10C] FIG. 10C shows the electrode energy density. [Figure 11A] FIG. 11A is a bar graph showing energy density for an embodiment of a silicon-containing anode electrode film according to Example 9. [Figure 11B] FIG. 11B is a bar graph showing the energy density increase for an embodiment of a silicon-containing anode electrode film according to Example 9. [Figure 12] FIG. 12 is an SEM image of the surface of an embodiment of a silicon-containing anode electrode film comprising 4.7 wt. % silicon nanoparticles according to Example 10. [Figure 13A] FIG. 13A is a graph showing the theoretical specific capacity for various fractions of Group 14 elements as constituents of a graphite anode film. [Figure 13B] FIG. 13B is a graph showing the specific capacity enhancement for various fractions of Group 14 elements as components of the graphite anode film. [Figure 14A] FIG. 14A is a graph of electrochemical charge and discharge capacity versus voltage of a silicon-containing anode electrode film compared to a control graphite film in an embodiment according to Example 12. [Figure 14B] FIG. 14B is a graph of the electrochemical charge and discharge capacity versus voltage of a tin-containing anode electrode film compared to a control graphite film in an embodiment according to Example 12. [Figure 15]FIG. 15 shows the ultimate tensile strength of a dry free-standing anode electrode film containing a Group 14 active material compared to a typical free-standing graphite film in an embodiment according to Example 13. [Figure 16A] FIG. 16A is a bar graph showing the charge and discharge capacities of prelithiated Li—SiO / C composite anodes tested at voltages from 5 mV to 2 V at a 0.05 C rate in an embodiment according to Example 14. [Figure 16B] FIG. 16B is a bar graph showing the efficiency of prelithiated Li—SiO / C composite anodes tested at voltages between 5 mV and 2 V at a 0.05 C rate in an embodiment according to Example 14. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Various embodiments of electrode films for use in energy storage devices are described. In particular, in certain embodiments, the energy storage devices disclosed herein include an anode electrode film comprising a silicon material. The electrode film exhibits improved mechanical and processing properties over typical silicon-containing electrode films. Also provided is a method for producing such an electrode film. The present invention reveals that the material of the electrode film can be realized when the particle size of certain components is within the ranges provided herein.
[0013] Lithium-ion batteries have been relied upon as the power source for many commercial and industrial applications, for example, in consumer devices, productivity equipment, and battery-powered vehicles. However, the demand for energy storage devices is continually and rapidly growing. For example, the automotive industry is developing vehicles that rely on small, efficient energy storage, such as plug-in hybrids and pure electric vehicles.
[0014] Group 14 metalloids and metals, such as tin and silicon, are known to be desirable high energy active materials for inclusion in the anode of an energy storage device. It is believed that one silicon atom can accommodate 4.4 equivalents of lithium ions. Theoretically, the material formed would be Li4.4 Si. Thus, in principle, a silicon anode material could store about 11 times the capacity (4200 mAh / g and 9782 mAh / L) of graphite (372 mAh / g). Silicon has been described as a high capacity anode material. Tin is another Group 14 element described herein as an anode active material.
[0015] However, some properties of group 14 metalloids and metals, especially silicon, present challenges in their implementation in practical devices. In particular, silicon is believed to undergo relatively large volume changes during lithiation and delithiation. Such changes can lead to loss of cohesion and / or adhesion of the electrode film upon cycling, which can lead to high contact resistance in the electrode and ultimately contribute to cell failure. Furthermore, silicon is typically incorporated into the electrode as nanoparticles. Such nanoparticles require a larger amount of binder to maintain the integrity of the film, and up to 30% by weight of binder may be required. Furthermore, wet manufacturing processes require a larger amount of solvent to suspend the nanoparticles. Thus, the incorporation of silicon, which is desired to improve electrode film capabilities, can reduce the stability and processability of the electrode film. Thus, there is a need for electrode films containing silicon that maintain cyclability and are compatible with industrial processing techniques.
[0016] Silicon materials may include nanoparticles, nanowires, and silicon / graphene composites. Silicon nanoparticle and nanowire anodes are expected to benefit from significantly higher binder loadings (~30 wt%) and solvents in wet electrode coating processes due to the large surface area of these materials. One approach to using silicon in anodes is to combine silicon with graphite to form a silicon / graphite composite. However, the silicon content in the silicon / graphite composite may be limited by material properties, such as volume expansion and achieving uniform dispersion of silicon, which are expected to affect the electrochemical performance of silicon / graphite composite electrodes.
[0017] An embodiment includes electrode films made with various electrode materials, such as graphite, silicon, silicon oxide, silicon-graphene, silicon-aluminum alloy, tin / graphene, and various polymer binders. Group 14 active materials, including silicon active materials, have been found to provide processable anode electrode films with increased energy storage capacity, along with graphite in the anode. An embodiment is a silicon-containing anode electrode film that includes a first graphite material having a grain size greater than about 10 μm and a second graphite material having a grain size less than about 10 μm.
[0018] The materials and methods described herein can provide the advantage of higher Si content in the composite anode electrode film, providing a high energy density electrode. The dry anode electrode film comprising the silicon / graphite composite anode active material described herein can provide an electrochemical charge capacity comparable to its theoretical charge capacity. Thus, the silicon active material in the dry silicon / graphite composite anode electrode film can be electrochemically active and accessible over charge / discharge cycles.
[0019] The terms "battery" and "capacitor" are given their ordinary and accustomed meaning to those of ordinary skill in the art. The terms "battery" and "capacitor" are not mutually exclusive. A capacitor or battery is a single electrochemical cell that may be operated alone or as a component of a multi-cell system.
[0020] The voltage of an energy storage device is the operating voltage of a single battery or capacitor cell. The voltage may exceed or fall below the rated voltage under load or according to manufacturing tolerances.
[0021] The term "self-supporting" electrode film is an electrode film that incorporates a binder matrix structure sufficient to support the film or layer and maintain its shape so that the electrode film or layer can be free-standing. When incorporated into an energy storage device, a self-supporting electrode film or active layer is one that incorporates such a binder matrix structure. Typically, and depending on the method used, such electrode films are strong enough to be employed in the manufacturing process of an energy storage device without the use of external support elements such as current collectors or other films. For example, a "self-supporting" electrode film can be strong enough to be rolled, handled, and unrolled during the electrode manufacturing process without other support elements. A dry electrode film, such as a cathode electrode film or an anode electrode film, may be self-supporting.
[0022] A "solvent-free" electrode film is one that does not contain any detectable process solvent, process solvent residue, or process solvent impurities. Dry electrode films, such as cathode or anode electrode films, can be solvent-free.
[0023] A "wet" electrode, "wet process" electrode or slurry electrode is an electrode prepared by at least one step involving a slurry of active material, binder, and optionally additives. Wet electrodes may contain process solvent, process solvent residues, and / or process solvent impurities.
[0024] A "non-destructive" process is one in which the electrode active material, including the surface of the electrode active material, is not substantially altered during the process. Thus, the analytical properties and / or performance of the active material in applications such as incorporation into an energy storage device are the same or nearly the same as those that have not been subjected to the process. For example, the coating on the active material may not be disturbed or substantially disturbed during the process. A non-limiting example of a non-destructive process is "non-destructive blending or mixing" and jet milling under reduced pressure, increasing the feed rate, decreasing the rate (e.g., blender speed), and / or varying other process parameters such that the shear applied to the active material remains below a threshold at which the analytical properties and / or performance of the active material are adversely affected when implemented in an energy storage device. A "non-destructive" process can be distinguished from a high shear process that substantially modifies the electrode active material, such as the surface of the electrode active material, and substantially affects the analytical properties and / or performance of the active material. For example, high shear blending or high shear jet milling may have a detrimental effect on the surface of the electrode active material. High shear processes can be carried out to provide other benefits, such as fibrillation of the binder material, or formation of a binder / active material matrix to aid in the formation of a self-supporting electrode film, without compromising the surface properties of the active material. Embodiments herein can provide similar benefits while avoiding the detrimental effects of excessive use of high shear processes. In general, non-destructive processes herein are carried out at one or more of higher feed rates, lower speeds, and / or lower pressures, resulting in a lower shear process than destructive processes that substantially alter the electrode active material and affect performance.
[0025] Silicon-containing self-supporting anode electrode film By optimizing the shape and size of the electrode material and varying the material composition in the electrode formulation, silicon and / or tin-containing electrodes with high energy density can be produced by dry processing methods. The graphite material can include artificial graphite, such as synthetic graphite, natural graphite, and mixtures of graphite. In general, the graphite material can have different properties such as mass ratio, particle size, particle shape, and raw material.
[0026] An embodiment is a free-standing and / or self-supporting silicon / graphite composite dry film having a high silicon content. The dry film can be produced by using two different sizes of graphite. The primary graphite may have a particle size of about 20-30 μm, and the secondary graphite material has a smaller particle size, for example, having a particle size of 4-7 microns. It has been found that the use of different sizes of graphite allows the use of relatively high silicon contents, up to 10-30 wt.%, to produce a strong thin dry film with roll-to-roll electrode processability.
[0027] In some embodiments, the anode electrode films provided herein include at least one active material and at least one binder. The at least one active material generally includes a Group 14 active material, such as a silicon active material and / or a tin active material, and at least one carbon-based material, such as a graphite material.
[0028] An embodiment is a method for producing a self-supporting anode electrode film comprising silicon that is produced when it comprises multiple graphite materials with different particle sizes. The graphite materials may be distinguishable by source, e.g., natural or artificial graphite, surface characteristics, particle size, surface area, and / or particle shape. In some embodiments, at least one primary graphite (PG) and at least one secondary graphite (SG) are included in the anode electrode film.
[0029] The at least one primary graphite and the at least one secondary graphite can be distinguished as having two different particle sizes. In some embodiments, the first average particle size (i.e., D 50 The silicon-containing electrode film includes at least one primary graphite having a grain size greater than about 10 μm and at least one secondary graphite having a smaller second average grain size. The at least one primary graphite may be an artificial or natural graphite having a grain size greater than about 10 μm. The at least one secondary graphite may be an artificial or natural graphite having a grain size less than 10 μm. In some embodiments, the at least one primary graphite has an average grain size of about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, or about 40 μm, or any value therebetween. In further embodiments, the at least one secondary graphite has an average grain size of about 1 μm, about 2 μm, about 3 μm, about 4 μm, about 5 μm, about 6 μm, about 7 μm, about 8 μm, about 9 μm, or about 10 μm, or any value therebetween. In certain embodiments, the at least one primary graphite has an average particle size of about 22-30 μm and the at least one secondary graphite has an average particle size of about 4-7 μm. In further embodiments, the anode electrode film comprises a first primary graphite and a second primary graphite in combination with the secondary graphite, as described above. In further embodiments, the anode electrode film comprises a first secondary graphite and a second secondary graphite in combination with the primary graphite, as described above. In further embodiments, the anode electrode film further comprises a third primary graphite and / or a third secondary graphite.
[0030] The anode electrode film can include primary graphite (PG) and secondary graphite (SG) in various mass ratios, such as PG:SG in the range of 10:1 to 1:10. In various embodiments, the PG:SG mass ratio can be, for example, about 10:1, about 8:1, about 6:1, about 5:1, about 4:1, about 3:1, about 2:1, about 1:1, about 1:2, about 1:3, about 1:4, about 1:5, about 1:6, about 1:8, or about 1:10, or any range of values therebetween.
[0031] Each of the at least one primary graphite and / or the at least one secondary graphite may be natural graphite or artificial graphite. Each of the at least one primary graphite and / or the at least one secondary graphite may be characterized by a particle shape, such as, for example, spherical, flaky, elliptical, or irregular. Each of the primary graphite and / or the secondary graphite may include a surface coating. In some embodiments, the at least one primary graphite comprises natural graphite or synthetic graphite. In further embodiments, the at least one secondary graphite comprises natural graphite or synthetic graphite.
[0032] The anode electrode film generally includes an anode active material. The anode active material may include at least one primary graphite, at least one secondary graphite, and a Group 14 active material, such as a silicon active material or a tin active material. The silicon active material in the anode electrode film may include pure silicon, silicon oxide, prelithiated silicon, or silicon-carbon composite. The silicon active material may be selected from pure silicon (Si), silicon oxide (SiO), silicon alloy, such as Si-Al or Si-Sn. The silicon active material may include a silicon-carbon composite. The silicon-carbon composite may be, for example, silicon graphene (SiC), silicon graphite (Si / C), silicon oxide graphene (SiOC), silicon oxide graphite (SiO / C), prelithiated silicon graphite, and prelithiated silicon graphene. In some embodiments, the prelithiated silicon graphite may be a prelithiated silicon oxide graphite composite. The silicon active material may be SiH. The silicon active material may be prelithiated silicon. Prelithiated silicon is Li x SiO y Or Li x S y The silicon active material may be incorporated into the electrode film as a nanoscale, i.e., about 1 nm to about 1000 nm, or microscale, i.e., about 1 μm to about 1000 μm. The silicon active material may include particles having a primary particle size of about 30 nm to about 10 μm. The silicon active material may include particles having a primary particle size of about 100 nm, about 250 nm, about 500 nm, about 1 μm, about 2 μm, about 4 μm, about 6 μm, about 8 μm, or about 10 μm, or any value therebetween. In some embodiments, the silicon active material is a commercially available material that is used without further processing.
[0033] In some embodiments, the anode electrode film comprises or comprises about 1 wt%, about 2 wt%, about 3 wt%, about 5 wt%, about 7.5 wt%, about 10 wt%, about 15 wt%, about 20 wt%, about 25 wt%, about 30 wt%, about 40 wt%, or about 50 wt% silicon, or any value therebetween. In further embodiments, the anode electrode film or anode electrode film mixture comprises or comprises about 1-30 wt% silicon, or 10-30 wt% silicon. In yet further embodiments, the anode electrode film or anode electrode film mixture comprises or comprises about 1-5 wt% silicon, or 5-15 wt% silicon. In some embodiments, the anode electrode film comprises or comprises about 1%, about 2%, about 3%, about 5%, about 7.5%, about 10%, about 15%, about 20%, about 25%, about 30%, about 40%, or about 50% by weight of the Group 14 active material, or any value therebetween. In further embodiments, the anode electrode film or anode electrode film mixture comprises or comprises about 1-30% by weight of the Group 14 active material, or 10-30% by weight of the Group 14 active material. In still further embodiments, the anode electrode film or anode electrode film mixture comprises or comprises about 1-5% by weight of the Group 14 active material, or 5-15% by weight of the Group 14 active material. Typically, anode electrode films that comprise a specified amount (e.g., percentage) of a Group 14 active material, such as silicon active material, comprise a specified amount of the Group 14 active material, with the remainder of the active material being graphite. Unless otherwise specified, the weight percent of Group 14 active material is based on the total weight of the electrode film, including the active material, binder, and any other additives.
[0034] Anode active materials, including silicon active materials and graphite, can be classified, for example, as intercalation materials (such as carbon, graphite, and / or graphene), alloyed / dealloyed materials (such as silicon, silicon oxide (SiOx), aluminum, tin, and / or tin oxide (SnOx)), metal alloys or compounds (such as Si-Al, and / or Si-Sn), and / or conversion materials (such as transition metal oxides, e.g., manganese oxide (MnOx), molybdenum oxide (MoO2), nickel oxide (NiOx), and / or copper oxide (CuOx)). The anode active materials can be used alone or mixed together to form multiphase materials (e.g., Si-C, Sn-C, SiOx-C, SnOx-C, Si-Sn, Si-SiOx, Sn-SnOx, Si-SnOx-C, Sn-SnOx-C, Si-Sn-C, SiOx-Sn, or Sn-SiOx-SnOx, etc.). The silicon active material can include nanoparticles. In some embodiments, the anode active material includes a single Group 14 active material. In further embodiments, the anode active material includes a single Group 14 element. In yet other embodiments, the anode active material includes multiple Group 14 elements. In still further embodiments, the anode active material includes silicon and tin.
[0035] The anode active material can include various combinations of silicon and graphite active materials, as shown in Tables 1, 2, and 3. As shown in each of the formulation examples in Tables 1, 2, and 3, the ratios of primary graphite, secondary graphite, and silicon active materials can be varied.
[0036] [Table 1]
[0037] [Table 2]
[0038] [Table 3]
[0039] The anode electrode films described herein can have a film thickness of at least 50 μm, e.g., about 50 μm, about 100 μm, about 150 μm, about 200 μm, about 225 μm, about 250 μm, about 275 μm, about 300 μm, or about 400 μm, or any value therebetween.
[0040] The anode electrode films described herein have a thickness of at least about 10 mg / cm 2 , for example, about 10 mg / cm 2 , about 15mg / cm 2 , about 20mg / cm 2 , about 25mg / cm 2 , about 30mg / cm 2 , about 35mg / cm 2 , about 40mg / cm 2 , or any value therebetween.
[0041] In some embodiments, the silicon-containing anode electrode film can provide a coulombic efficiency of about 75%, about 78%, about 80%, about 82%, about 84%, about 86%, about 88%, about 90%, about 92%, about 94%, or any value therebetween.
[0042] In some embodiments, the silicon-containing anode electrode film can provide an energy density (which can be expressed as energy per mass of the electrode film) of about 1000 Wh / kg, about 1200 Wh / kg, about 1400 Wh / kg, about 1600 Wh / kg, about 1800 Wh / kg, about 2000 Wh / kg, or any range of values therebetween.
[0043] In some embodiments, the silicon-containing anode electrode film can provide a specific energy storage (which can be expressed as energy per unit volume of the final or in situ electrode film) of about 2000 Wh / L, about 3000 Wh / L, about 4000 Wh / L, about 5000 Wh / L, or any range of values therebetween.
[0044] In some embodiments, the silicon-containing anode electrode film may provide a specific capacity upon charge or discharge of about 400 mAh / g, about 500 mAh / g, about 600 mAh / g, about 700 mAh / g, about 800 mAh / g, about 1000 mAh / g, about 1500 mAh / g, about 2000 mAh / g, about 3000 mAh / g, or any value therebetween.
[0045] In some embodiments, a silicon-containing anode electrode film may provide a measured specific capacitance of at least 95% of its theoretical capacity, for example, about 95%, about 96%, about 97%, about 98%, about 99%, about 99.9%, or any value therebetween.
[0046] The one or more binders may include polytetrafluoroethylene (PTFE), polyolefins, polyalkylenes, polyethers, styrene butadiene rubber (SBR), polysiloxanes and copolymers of polysiloxanes, branched polyethers, polyvinyl ethers, polyacrylic acid, polyvinyl carbonate, copolymers thereof, and / or mixtures thereof. The one or more binders may further include guar, alginic acid, poly[(isobutylene-alt-maleic acid, ammonium salt)-co-isobutylene-alt-maleic anhydride], poly(ethylene-alt-maleic anhydride), poly(methyl vinyl ether-alt-maleic anhydride), polyacrylonitrile (PAN), poly(methyl methacrylate) (PMMA), poly(vinyl chloride) (PVC), and polyvinyl ether. The binder may include cellulose. In some embodiments, the polyolefin may include polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), copolymers thereof, and / or mixtures thereof. For example, the binder may include polyvinylene chloride, poly(phenylene oxide) (PPO), polyethylene-block-poly(ethylene glycol), poly(ethylene oxide) (PEO), poly(phenylene oxide) (PPO), polyethylene-block-poly(ethylene glycol), polydimethylsiloxane (PDMS), polydimethylsiloxane-carbon alkyl methyl siloxane, copolymers thereof, and / or mixtures thereof. In certain embodiments, the fibrillizable binder is PTFE. The dry self-supporting electrode film may include an interpenetrating network of the aforementioned binders.
[0047] The binder may include cellulose or a derivative of cellulose. The derivative of cellulose may include, for example, a cellulose ester such as cellulose acetate; a cellulose ether such as methyl cellulose, ethyl cellulose, hydroxypropyl cellulose (HPC), hydroxypropyl methyl cellulose, or hydroxyethyl cellulose (HEC); a cellulose nitrate; a cellulose chitosan such as carboxymethyl cellulose chitosan; or a carboxyalkyl cellulose such as carboxymethyl cellulose (CMC), carboxyethyl cellulose, carboxypropyl cellulose, or carboxyisopropyl cellulose. In further embodiments, the cellulose or a derivative of cellulose may include a cellulose salt. In still further embodiments, the cation of the cellulose salt may be selected from sodium, ammonium, calcium, or lithium. For example, the cellulose or a derivative of cellulose may include sodium cellulose or a derivative of sodium cellulose selected from sodium cellulose ester, sodium cellulose ether, sodium cellulose nitrate, or sodium carboxyalkyl cellulose. The CMC may include sodium carboxymethyl cellulose. In some embodiments, one or more binders include CMC, PVDF, and / or PTFE.
[0048] In some embodiments, the silicon-containing anode electrode films provided herein include a graphite material selected for such films. In some embodiments, a graphite-containing formulation is provided to enable dry electrode processing of the silicon-containing anode electrode films provided herein. In further embodiments, the anode electrode film is a free-standing film. In some embodiments, the silicon-containing anode electrode films provided herein include a silicon mass loading of more than 10 wt. %. In some embodiments, the silicon-containing anode electrode films provided herein include a non-aqueous carbonate-based electrolyte to improve performance.
[0049] The electrode films described herein, or energy storage devices incorporating the electrode films described herein, can be advantageously characterized by improved specific capacity (which may be measured in mAh / g). Further improvements that can be realized in various embodiments include reduced degradation over the life of the device, as compared to typical silicon-containing electrode films.
[0050] The free-standing anode electrode films described herein can have improved ultimate tensile strength (which can be measured in Newtons (N) from a film having a width of 20 millimeters). In some embodiments, the ultimate tensile strength of the anode electrode film is at least about 2 N, e.g., about 2 N, about 2.5 N, about 3 N, about 3.5 N, about 4 N, or any value therebetween.
[0051] Some embodiments relate to dry electrode processing techniques. Dry electrode manufacturing processes may be those disclosed in one or more of U.S. Patent Application Publication No. 2006 / 0114643, U.S. Patent Application Publication No. 2006 / 0133013, U.S. Patent No. 9,525,168, or U.S. Patent No. 7,935,155, each of which is incorporated herein by reference in its entirety.
[0052] In some embodiments, a method for producing a free-standing electrode film is provided. With reference to FIG. 2, method 200 can include selecting a group 14 active material (205), combining (e.g., mixing) the group 14 active material with one or more graphitic materials, such as a first and a second graphitic material, to form an active material mixture (210), mixing the active material mixture with a binder to form an electrode film mixture (215), and calendaring the electrode film mixture to form a self-supporting and / or free-standing electrode film (220). Step 210 can include blending or grinding the group 14 active material and graphite to disperse the particles. In some embodiments, each step is dry and solvent-free. In a further embodiment, the group 14 active material is a silicon active material. In yet a further embodiment, the binder is a fibrillizable binder, such as PTFE. Some embodiments can include a premixing step prior to step 210, including premixing the dry group 14 active material with the dry binder. The dry binder used in such a premixing step may be the same or a different material as the binder used in step 215.
[0053] In various embodiments, a mixture including dry powders, e.g., binder particles and / or active material particles, can be formed by a gentle step (e.g., in steps 210, 215, or the aforementioned premixing step of method 200) using, e.g., a convection, pneumatic, or diffusion mixer, such as a tumbler, paddle mixer, blade blender, or acoustic mixer, with and without a mixing medium (e.g., glass beads, ceramic balls). The gentle mixing process can be non-destructive with respect to any active material in the mixture. Without being limited thereto, graphite particles and / or silicon active material particles may be size-preserved after the gentle mixing process. In further embodiments, the sequence and conditions of powder mixing can be altered to improve uniform distribution of the active material, binder, and any additives. The gentle premixing can also enhance the structural stability of Group 14 active materials, such as silicon, during cycling of the energy storage device.
[0054] In various embodiments, a dry powder, such as a mixture including binder particles and / or active material particles, can be formed (e.g., in steps 210, 215, or the aforementioned premixing step of method 200) by a high shear step, such as high shear blending or high shear jet milling. High shear premixing can enhance contact between the Group 14 active material, such as silicon, and the one or more binders. In further embodiments, the sequence and conditions of powder mixing may be altered to improve uniform distribution of the active material, binder, and any additives.
[0055] The materials and methods provided herein can be implemented in various energy storage devices. As provided herein, the energy storage device can be a capacitor, a lithium ion capacitor (LIC), an ultracapacitor, a battery such as a lithium ion battery, or a hybrid energy storage device that combines two or more of the above aspects. In a preferred embodiment, the device is a lithium ion battery.
[0056] The energy storage devices provided herein may be in any suitable shape, such as flat, spirally wound, button-shaped, or pouch. The energy storage devices provided herein may be components of a system, such as a power generation system, an uninterruptible power supply system (UPS), a solar power generation system, an energy recovery system, such as used in industrial machinery and / or transportation. The energy storage devices provided herein may be used to power a variety of electronic devices and / or automobiles, including hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and / or electric vehicles (EVs).
[0057] 1 shows a cross-sectional schematic side view of an example of an energy storage device 100 having an electrode film, including a silicon-containing anode electrode film provided herein. The energy storage device 100 can be classified as, for example, a capacitor, a battery, a capacitor-battery hybrid, or a fuel cell. In a preferred embodiment, the device 100 is a lithium ion battery.
[0058] The device has a silicon-based anode 102, a cathode 104, and a separator 106 disposed between the anode 102 and the cathode 104. The anode 102 and the cathode 104 are adjacent to respective opposing surfaces of the separator 106. The energy storage device 100 includes an electrolyte 118 for facilitating ionic communication between the anode 102 and the cathode 104 of the energy storage device 100. The electrolyte 118, anode 102, cathode 104, and separator 106 are contained within an energy storage device housing 120.
[0059] The energy storage device housing 120 may be sealed around the first electrode 102, the second electrode 104, and the separator 106, and may be physically sealed from the surrounding environment.
[0060] The separator 106 is configured to electrically insulate the anode 102 from the cathode 104 while allowing ionic communication between the two adjacent electrodes. The separator 106 can include a suitable porous, electrically insulating material. In some embodiments, the separator 106 can include a polymeric material. For example, the separator 106 can include a cellulosic material (e.g., paper), a polyethylene (PE) material, a polypropylene (PP) material, and / or a polyethylene and polypropylene material.
[0061] Generally, the anode 102 and the cathode 104 each include a current collector and an electrode film. For example, the anode 102 includes an electrode film 112, and the cathode 104 includes an electrode film 114, respectively. The electrode films 112 and 114 can have any suitable shape, size, and thickness. For example, the electrode film can have a thickness of about 30 microns (μm) to about 250 microns, e.g., about 50 microns, about 100 microns, about 150 microns, about 200 microns, about 250 microns, about 300 microns, about 400 microns, about 500 microns, about 750 microns, about 1000 microns, about 2000 microns, or values therebetween. The electrode film generally includes one or more active materials, e.g., an anode active material or a cathode active material provided herein. The electrode films 112 and / or 114 may be dry and / or self-supporting electrode films as provided herein and may have beneficial properties such as tensile strength or capacitance as provided herein. The first electrode film 112 and / or the second electrode film 114 may include a group 14 active material, such as silicon active material, as described herein. As shown, the first electrode film 112 includes silicon active material particles 122 and graphite active material particles 124. The electrode films 112 and / or 114 may be prepared by methods as described herein. The electrode films 112 and / or 114 may be wet electrodes or self-supporting dry electrodes as described herein.
[0062] The first current collector 108 and the second current collector 110 facilitate electrical coupling between each corresponding electrode film and an external electrical circuit (not shown). The first current collector 108 and / or the second current collector 110 can comprise one or more conductive materials and have any suitable shape and size selected to facilitate transfer of charge between the corresponding electrode and the external circuit. For example, the current collectors can include metallic materials such as aluminum, nickel, copper, rhenium, niobium, tantalum, and materials including precious metals, such as silver, gold, platinum, palladium, rhodium, osmium, iridium, and alloys and combinations thereof. For example, the first current collector 108 and / or the second current collector 110 can include, for example, aluminum foil or copper foil. The first current collector 108 and / or the second current collector 110 can have a rectangular or substantially rectangular shape sized to provide for the transfer of charge between the corresponding electrode and an external circuit.
[0063] In some embodiments, the energy storage device 100 can be a lithium ion battery. In some embodiments, the electrode film of a lithium ion battery electrode can include a silicon active material.
[0064] In further embodiments, the energy storage device 100 is charged with a suitable lithium-containing electrolyte. For example, the device 100 can include a lithium salt and a solvent, such as a non-aqueous or organic solvent. Generally, the lithium salt includes a redox stable anion. In some embodiments, the anion can be monovalent. In some embodiments, the lithium salt can be selected from hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), lithium bis(fluorosulfonyl)imide (F2NO4S2Li), lithium trifluoromethanesulfonate (LiSO3CF3), lithium bis(oxalato)borate (LiBC2O4)2, and combinations thereof. In some embodiments, the electrolyte can include a quaternary ammonium cation and an anion selected from the group consisting of hexafluorophosphate, tetrafluoroborate, and iodide. In some embodiments, the salt concentration may be about 0.1 mol / L (M) to about 5 M, about 0.2 M to about 3 M, or about 0.3 M to about 2 M. In further embodiments, the salt concentration of the electrolyte may be about 0.7 M to about 1 M. In certain embodiments, the salt concentration of the electrolyte may be about 0.2 M, about 0.3 M, about 0.4 M, about 0.5 M, about 0.6 M, about 0.7 M, about 0.8 M, about 0.9 M, about 1 M, about 1.1 M, about 1.2 M, or any value therebetween.
[0065] In some embodiments, the energy storage device electrolyte provided herein can include a liquid solvent. The solvent provided herein does not need to dissolve all components of the electrolyte, and does not need to completely dissolve any components. In further embodiments, the solvent can be an organic solvent. In some embodiments, the solvent can include one or more functional groups selected from carbonates, ethers, and / or esters. In some embodiments, the solvent can include a carbonate. In further embodiments, the carbonate can be selected from cyclic carbonates, such as, for example, ethylene carbonate (EC), propylene carbonate (PC), vinyl ethylene carbonate (VEC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), and combinations thereof, or acyclic carbonates, such as, for example, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and combinations thereof. In certain embodiments, the electrolyte can include LiPF6 and one or more carbonates.
[0066] In some embodiments, the electrolyte solvent comprises ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and propylene carbonate (PC). In further embodiments, the electrolyte solvent comprises ethylene carbonate (EC) and dimethyl carbonate (DMC). In yet further embodiments, the electrolyte solvent comprises ethylene carbonate (EC) and ethyl methyl carbonate (EMC). In further embodiments, the electrolyte solvent comprises ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). The electrolyte solvent may comprise an ethyl methyl carbonate-rich solvent blend. The electrolyte may further comprise an additive. The electrolyte additive may be a carbonate, such as fluoroethylene carbonate (FEC) or diallyl pyrocarbonate (DAPC). The electrolyte additive may be cyclohexane (CH). The electrolyte solvent can contain about 1% by mass to about 30% by mass, for example, about 1% by mass to about 20% by mass or about 1% by mass to about 10% by mass of the additive.
[0067] Table 4 provides embodiments of electrolyte formulations including a carbonate solvent, a lithium salt, and one or more additives, where the one or more additives were FEC, CH, and / or DAPC. Particular embodiments provide each of electrolytes 1-4 in which the volume ratio of EC:EMC is about 3:7. Further embodiments provide each of electrolytes 1-4 in which the LiPF6 salt concentration is about 1.2M. In Table 4, the weight percent of each additive is based on the total weight of the electrolyte, including the solvent, salt, and additive.
[0068] [Table 4]
[0069] The materials and methods provided herein can be implemented in a variety of energy storage devices. As provided herein, the energy storage device can be a capacitor, a lithium ion capacitor (LIC), an ultracapacitor, a battery, or a hybrid energy storage device and / or a hybrid cell, and can combine two or more aspects thereof. In a preferred embodiment, the device is a battery. The energy storage device can be characterized by an operating voltage. In some embodiments, the energy storage device described herein can have an operating voltage of about 0V to about 5V. In further embodiments, the operating voltage can be about 2.7V to about 4.2V, about 3.0V to about 4.2V, or a value therebetween.
[0070] In some embodiments, the lithium ion batteries are configured to operate between about 2.5 and 5 V, i.e., between 3.0 and 4.2 V. In further embodiments, the lithium ion batteries are each configured to have a minimum operating voltage between about 2.5 V and about 3 V. In yet other embodiments, the lithium ion batteries are each configured to have a maximum operating voltage between about 4.1 V and about 4.4 V.
[0071] In some embodiments, the electrode film provided herein comprises at least one active material and at least one binder. The at least one active material can be any active material known in the art. The at least one active material can be a material suitable for use in the anode or cathode of a battery. The cathode active material can be, for example, a metal oxide, a metal sulfide, a sulfur-carbon composite, or a lithium metal oxide. The lithium metal oxide can be, for example, lithium nickel manganese cobalt oxide (NMC), lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium cobalt oxide (LCO), lithium titanate (LTO), lithium nickel manganese oxide (LNMO), and / or lithium nickel cobalt aluminum oxide (NCA). In some embodiments, the cathode active material can be, for example, a layered transition metal oxide (LiCoO2 (LCO), Li(NiMnCo)O2 (NMC), and / or LiNi 0.8 Co 0.15 Al 0.05 O2 (NCA), spinel manganese oxides (LiMn2O4 (LMO) and / or LiMn 1.5 Ni 0.5 04 (such as LMNO) or olivine (such as LiFePO4). The cathode active material can include sulfur or a material containing sulfur, such as lithium sulfide (Li2S), or other sulfur-based materials, or mixtures thereof. In some embodiments, the cathode film includes sulfur or a material including at least 50% by weight of a sulfur active material. In some embodiments, a cathode film including sulfur or a material including a sulfur active material has a capacity of at least 10 mAh / cm 2 In some embodiments, a cathode film comprising a material comprising sulfur or a sulfur active material has an area-normalized specific capacitance (i.e., area capability) of 1 g / cm 3 In some embodiments, the cathode film comprising a material comprising sulfur or a sulfur active material further comprises a binder.
[0072] The at least one active material may include one or more carbon materials, which may be selected from, for example, graphitic materials, graphite, graphene-containing materials, hard carbon, soft carbon, carbon nanotubes, porous carbon, conductive carbon, or combinations thereof. The graphite may be synthetic or naturally derived. Activated carbon may be obtained from a water steam process or an acid / etching process. In some embodiments, the graphitic material may be a surface treated material. In some embodiments, the porous carbon may comprise activated carbon. In some embodiments, the porous carbon may comprise hierarchical structured carbon. In some embodiments, the porous carbon may comprise structured carbon nanotubes, structured carbon nanowires and / or structured carbon nanosheets. In some embodiments, the porous carbon may comprise graphene sheets. In some embodiments, the porous carbon may be a surface treated carbon.
[0073] In some embodiments, the cathode electrode film of the lithium ion battery or hybrid energy storage device can comprise about 70% to about 98% by weight, including about 70% to about 92% by weight, or about 70% to about 96% by weight, of at least one active material. In some embodiments, the cathode electrode film can comprise up to about 10% by weight, including up to about 5% by weight, or about 1% to about 5% by weight, of a porous carbon material. In some embodiments, the cathode electrode film can comprise up to about 5% by weight, including about 1% by weight to about 3% by weight, of a conductive additive. In some embodiments, the cathode electrode film can comprise up to about 20% by weight of a binder, for example, about 1.5% to 10% by weight, about 4% to 10% by weight, about 1.5% to 5% by weight, or about 1.5% to 3% by weight. In some embodiments, the cathode electrode film can comprise about 1.5% to about 3% by weight of a binder.
[0074] In some embodiments, the anode electrode film can include at least one active material, a binder, and optionally a conductive additive. In some embodiments, the conductive additive can include a conductive carbon additive, such as carbon black. In some embodiments, the at least one active material of the anode can include synthetic graphite, natural graphite, hard carbon, soft carbon, graphene, mesoporous carbon, silicon, silicon oxide, tin, tin oxide, germanium, lithium titanate, mixtures, or composites of the aforementioned materials. In some embodiments, the anode electrode film can include about 80% to about 98% by weight, including about 80% to about 98% by weight, or about 94% to about 97% by weight, of the at least one active material. In some embodiments, the anode electrode film can include up to about 5% by weight, including about 1% to about 3% by weight, of the conductive additive. In some embodiments, the anode electrode film comprises up to about 20% by weight of the binder, including about 1.5% to 10% by weight, about 4% to 10% by weight, about 1.5% to 5% by weight, or about 3% to 5% by weight. In some embodiments, the anode electrode film comprises about 4% by weight of the binder. In some embodiments, the anode film can be free of conductive additives.
[0075] The one or more binders can include polytetrafluoroethylene (PTFE), polyolefins, polyalkylenes, polyethers, styrene-butadiene, polysiloxanes and copolymers of polysiloxanes, branched polyethers, polyvinyl ethers, polyacrylic acids, copolymers thereof, and / or mixtures thereof. The binder can include cellulose. In some embodiments, the polyolefin can include polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), copolymers thereof, and / or mixtures thereof. For example, the binder can include polyvinylene chloride, poly(phenylene oxide) (PPO), polyethylene-block-poly(ethylene glycol), poly(ethylene oxide) (PEO), poly(phenylene oxide) (PPO), polyethylene-block-poly(ethylene glycol), polydimethylsiloxane (PDMS), polydimethylsiloxane-coalkylmethylsiloxane, copolymers thereof, and / or mixtures thereof. In certain embodiments, the fibrillizable binder is PTFE. The dry self-supporting electrode film can include an interpenetrating network of the aforementioned binders.
[0076] The binder may include cellulose or a derivative of cellulose. The derivative of cellulose may include, for example, a cellulose ester such as cellulose acetate; a cellulose ether such as methyl cellulose, ethyl cellulose, hydroxypropyl cellulose (HPC), or hydroxyethyl cellulose (HEC); a cellulose nitrate; or a carboxyalkyl cellulose, for example, carboxymethyl cellulose (CMC), carboxyethyl cellulose, carboxypropyl cellulose, or carboxyisopropyl cellulose. In further embodiments, the cellulose or a derivative of cellulose may include a cellulose salt. In still further embodiments, the cation of the cellulose salt may be selected from sodium, ammonium, or lithium. For example, the cellulose or a derivative of cellulose may include sodium cellulose or a derivative of sodium cellulose selected from sodium cellulose ester, sodium cellulose ether, sodium cellulose nitrate, or sodium carboxyalkyl cellulose. The CMC may include sodium carboxymethyl cellulose. In some embodiments, one or more binders include CMC, PVDF, and / or PTFE.
[0077] The electrode film mixture can include binder particles having a selected size, such as polytetrafluoroethylene binder particles. In some embodiments, the binder particles can be about 50 nm, about 100 nm, about 150 nm, about 200 nm, about 250 nm, about 300 nm, about 350 nm, about 400 nm, about 450 nm, about 500 nm, about 1 μm, about 2 μm, about 3 μm, about 4 μm, about 5 μm, about 10 μm, about 50 μm, about 100 μm, or values therebetween.
[0078] A dry manufacturing process can refer to a process that does not use or does not substantially use a solvent to form the electrode film. For example, the components of the electrode film, including the active material and the binder, can include dry particles. The dry particles for forming the electrode film can be combined to provide a dry particle electrode film mixture. In some embodiments, the electrode film can be formed from the dry particle electrode film mixture such that the weight percentages of the components of the electrode film and the weight percentages of the components of the dry particle electrode film mixture are substantially the same. In some embodiments, the electrode film formed from the dry particle electrode film mixture using a dry manufacturing process can be free or substantially free of processing additives such as solvents and solvent residues resulting therefrom. In some embodiments, the resulting electrode film is a self-supporting film formed from the dry particle mixture using a dry process. In some embodiments, the resulting electrode film is a free-standing film formed from the dry particle electrode film mixture using a dry process. A method for forming an active layer or electrode film can include fibrillating a fibrillizable binder component such that the film comprises a fibrillated binder matrix. In further embodiments, a free-standing electrode film may be formed in the absence of a current collector. In yet further embodiments, the electrode film may include a fibrillated polymer matrix such that the film is self-supporting. It is believed that a matrix, lattice, or web of fibrils may be formed to provide mechanical structure to the electrode film.
[0079] The electrode film can have a selected thickness suitable for a particular application. The thickness of the electrode film provided herein can be greater than that of electrode films prepared by conventional processes. In some embodiments, the electrode film can have a thickness of about 250 microns, about 300 microns, about 350 microns, about 400 microns, about 450 microns, about 500 microns, about 750 microns, about 1 mm, or about 2 mm, or any value therebetween. In some embodiments, the thickness of the electrode film can be varied to correspond to a selected volumetric energy density.
[0080] In the following examples, anode electrode films were fabricated and tested.
[0081] example Preparation of composite dry electrodes: Silicon / graphite composite dry electrodes of the embodiment were prepared by dry powder mixing graphite and silicon with electrode components, calendaring to form a free-standing film, and then laminating on a current collector. Dry powder mixing was performed in the following order: graphite / polymer binder / silicon. Specifically, dry powder mixing was performed using a resonant acoustic mixer at 50% acceleration as follows: primary and secondary graphite, and any group 14 active materials were mixed for 5 minutes, and then CMC, PVDF, and PTFE were added to the graphite mixture with continuous mixing. The dry mixed powders were processed through a micronizing jet mill with a feed of 40 psi and a grinding pressure of 40 psi, and then calendared at 100°C to 185°C to form a free-standing film.
[0082] Electrochemical characterization: A monolayer anode / lithium foil half-cell was assembled into a pouch cell configuration to perform electrochemical measurements. Electrochemical measurements were performed by applying a constant current and / or a constant potential to the anode half-cell at ambient temperature.
[0083] Example 1 3 is a graph showing the specific capacity of an exemplary silicon and graphite composite anode electrode film compared to the theoretical specific capacity of the films. Theoretical specific capacity was determined assuming a capacity of 370 mAh / g for graphite and 4200 mAh / g for silicon.
[0084] Example 2 In the embodiment of Fig. 4A-4C, commercially available artificial graphite (AG) and natural graphite (NG) were used to fabricate silicon / graphite composite electrodes prepared by a dry manufacturing process. Surprisingly, in the embodiment of Fig. 4A-4C, artificial graphite provided higher electrochemical capacity than natural graphite in silicon / graphite composite half-cells, along with slightly lower coulombic efficiency than natural graphite in the half-cell configuration. A more uniform distribution of silicon powder and interconnection between artificial graphite powder and silicon nanoparticles may play a role. In the embodiment of Fig. 4A-4C, natural graphite provided higher coulombic efficiency than artificial graphite. Fig. 4A shows electrochemical capacity, Fig. 4B shows coulombic efficiency, and Fig. 4C shows energy density for surface-modified artificial graphite / 10 wt% Si ("AG") and natural graphite / 10 wt% Si ("NG") composite anode electrode half-cells. The active material loadings were as follows: AG: 23.5 mg / cm 2 , NG: 25 mg / cm 2 .
[0085] Example 3 FIG. 5 provides the electrochemical specific capacity and coulombic efficiency of a graphite dry electrode ("0 wt% Si") compared to two embodiments of silicon / graphite dry electrodes containing 5 wt% ("5 wt% Si") and 10 wt% Si ("10 wt% Si"), respectively. The graphite in both cases was artificial graphite. As expected, the silicon / graphite dry electrode containing 10 wt% silicon (as Si) had the highest specific capacity and energy density. The increase in specific capacity of the 10 wt% silicon graphite composite relative to the 5 wt% silicon-containing graphite composite electrode was also proportional to the silicon content of each electrode, suggesting that the silicon active material powder was well dispersed and active under the conditions of the dry electrode processing method described herein. The active material loading was 0 wt% Si: 24.5 mg / cm 2 , 5wt%Si: 24.6mg / cm 2 , 10wt%Si:23.5mg / cm 2 It was decided.
[0086] Example 4 6A-6C show the electrochemical performance of Si / PG / SG composite dry electrode half cells with 10 wt% silicon (Si) according to formulations 2, 3, and 4 of Table 1. For each embodiment, FIG. 6A provides the capacity, FIG. 6B provides the efficiency, and FIG. 6C provides the electrode energy density. The results showed that the selection of primary graphite affects the electrochemical capacity and coulombic efficiency of the composite electrode. In this embodiment, natural graphite improved the electrochemical performance and energy density. The active material loading was as follows: Formulation 2: 22.5 mg / cm 2 , combination 3:24.6mg / cm 2 , combination 4:22.5mg / cm 2 .
[0087] Example 5 Figures 7A-7C show the electrochemical performance of silicon / graphene (SiC) containing SiC / PG / SG composite dry electrode half-cells according to formulation 1, containing 15 wt% silicon active material. Electrode films were prepared with PG:SG ratios of 1:1, 1:2, 1:3 and 1:4. Both PG and SG contained artificial graphite in their respective films. Corresponding to each embodiment, Figure 7A provides the capacity, Figure 7B provides the efficiency and Figure 7C provides the electrode energy density. The results show that the change in the mass ratio of PG:SG has little effect on the specific capacity and efficacy of this series of composite dry electrodes. The volumetric energy density is governed by the overall electrode thickness. As such, the thickness can be modified in the electrode fabrication steps for better placement of the volumetric energy density. The active material loadings were as follows: 1:1 film: 12.7 mg / cm 2 , 1:2 film: 12.5 mg / cm 2 , 1:3 film: 11 mg / cm 2 , 1:4 film: 11.6 mg / cm 2 .
[0088] Example 6 8A-8C show the electrochemical performance of PG(AG) / SG(AG) composite dry electrode half-cells containing silicon ("Si"), silicon / graphene ("SiC") and silicon oxide ("SiO") according to Formulation 1. Electrode films were prepared with a PG:SG ratio of 3:1. Both PG and SG contained artificial graphite. The Si film contained 10% Si, the SiC film contained 15% SiC and the SiO film contained 10% SiO. For each embodiment, FIG. 8A provides the capacity, FIG. 8B provides the efficiency and FIG. 8C provides the electrode energy density. The active material loadings were Si film: 22.5 mg / cm. 2 ,SiC film: 12.5mg / cm 2 , SiO film: 17 mg / cm 2 It was decided.
[0089] Example 7 FIG. 9 shows the ultimate tensile strength of various silicon / graphite composite dry films compared to a standard graphite dry film. The films tested were free-standing dry electrode films and contained various negative electrode active materials. The films tested included natural graphite film ("NG"), artificial graphite film ("AG"), artificial graphite film with 10% silicon ("as Si") by weight ("10% Si / AG"), natural graphite film with 10% silicon ("as Si") by weight ("10% Si / NG"), and film with artificial graphite and natural graphite and 10% silicon ("as Si") by weight ("10% Si / AG / NG"). The thicknesses of the films were as follows: NG film: 264 μm, AG film: 260 μm, 10 wt% Si / AG film: 248 μm, 10 wt% Si / NG film: 311 μm, 10 wt% Si / AG / NG film: 292 μm. The results showed improved tensile strength of the silicon / graphite composite dry films compared to the plain graphite film. Furthermore, the anode films containing PG and SG improved the elasticity and flexibility of the free-standing dry silicon-containing composite films along with the observed increase in tensile strength.
[0090] Example 8 Figures 10A-10C provide the electrochemical performance and energy density of four composite dry electrode films of SiO / PG / SG containing 10 wt% silicon active material as half cells and using electrolyte formulations listed in Table 4. Corresponding to each example, Figure 10A provides the capacity, Figure 10B provides the efficiency, and Figure 10C provides the electrode energy density. The results show that the electrolyte composition affects the electrochemical capacity and coulombic efficiency, leading to high energy density of silicon / graphite composite dry electrodes. The active material loadings were as follows: Electrolyte 1 film: 19.2 mg / cm 2 , electrolyte 2 film: 17.5 mg / cm 2 , electrolyte 3 film: 21 mg / cm 2 , electrolyte 4 film: 19.2 mg / cm 2 .
[0091] Example 9 11A and 11B provide additional performance data for silicon-containing anode electrode films. The films tested were free-standing dry electrode films and contained silicon-containing anode active materials. The films tested included a typical graphite anode electrode film ("0 wt.% Si"), a 4.7 wt.% silicon / graphite film ("4.7 wt.% Si"), and a 10 wt.% silicon / graphite film ("10 wt.% Si"). FIGS. 11A and 11B demonstrate that the silicon-containing films provide greater energy density than the typical graphite anode electrode film.
[0092] Example 10 FIG. 12 provides an SEM image of the surface of a silicon-containing anode electrode film containing 4.7 wt % nanoparticulate silicon.
[0093] Example 11 13A and 13B are graphs showing the theoretical increase in capacity corresponding to various fractions of Group 14 elements as constituents of a graphite anode film. Theoretically, as little as 3% silicon can increase capacity by about 33% over a typical graphite anode.
[0094] Example 12 14A and 14B provide graphs of electrochemical charge and discharge capacity versus voltage for silicon and tin-containing anode electrode films, respectively, compared to a typical graphite film ("Control"). The group 14 element containing films tested included graphite with 4.7 wt.% silicon ("4.7 wt.% Si-C") or 4.7 wt.% tin ("4.7% Sn-C"). Both the silicon-containing and tin-containing films had improved capacity compared to the typical graphite control film. In the case of silicon, this increase correlates with the extended plateau near 0.4V-0.5V in the charge cycle graph shown in FIG. 14A.
[0095] Example 13 FIG. 15 provides the maximum tensile strength of dry free-standing anode electrode films containing Group 14 active materials compared to a typical free-standing graphite film ("Control"). The films tested included a first graphite film containing silicon nanoparticles ("Si-C") and a second graphite film containing tin nanoparticles ("Sn-C"). The silicon-containing film had the highest measured tensile strength.
[0096] Example 14 Prelithiated silicon oxide graphite (SiO / C) half cells were prepared and tested. Table 5 shows the commercially available prelithiated SiO / C, types A to C, that were purchased. Type C has similar physical properties to type B without a surface coating, while types A and B have a surface coating.
[0097] [Table 5]
[0098] Each type of prelithiated SiO / C was used to fabricate electrodes according to the formulations detailed in Table 6. Resonant acoustic mixing at 60% intensity for 5 minutes was followed by dry powder mixing. The dry mixed powders were jet milled with 40 psi feed and 40 psi grind. The final formulations were calendered at room temperature, 50° C., to form free-standing films, which were subsequently laminated onto current collectors at 185° C. All calendering and lamination steps were carried out in a dry room.
[0099] [Table 6]
[0100] For the prelithiated Li-SiO / C composite anodes of Formulations 1-3 tested at 0.05C rate with voltages from 5 mV to 2 V, FIG. 16A provides a bar graph showing the charge / discharge capacity and FIG. 16B provides a bar graph showing the efficiency. The B-type prelithiated SiO / C anode of Formulation 2 showed slightly higher efficiency, which may be attributed to a slightly lower surface area, indicating that the non-surface-coated prelithiated SiO / C may be processed through a dry coating process. The active material loadings were as follows: Formulation 1: 20.4 mg / cm 2 , combination 2: 18.9mg / cm 2 , Formulation 3: 17.8mg / cm 2 .
[0101] Although specific embodiments of the present invention have been described, these embodiments are presented by way of example only and are not intended to limit the scope of the present disclosure. Indeed, the novel methods and systems described herein may be embodied in various other forms. Furthermore, various omissions, substitutions, and modifications in the systems and methods described herein may be made without departing from the spirit of the present disclosure. The appended claims and their equivalents are intended to cover such forms or modifications as fall within the scope and spirit of the present disclosure. Thus, the scope of the present invention is defined solely by reference to the appended claims.
[0102] Features, materials, properties, or groups described in connection with a particular aspect, embodiment, or example should be understood to be applicable to any other aspect, embodiment, or example described in this section or elsewhere in this specification, unless incompatible. All features disclosed herein (including any accompanying claims, abstract, and drawings), and / or all steps of any method or process so disclosed, may be combined in any combination, except where at least some of such features and / or steps are mutually exclusive. Protection is not limited to the details of the foregoing embodiments. Protection extends to any novel one, or any novel combination, of features disclosed herein (including any accompanying claims, abstract, and drawings), or any novel one, or any novel combination of steps of any method or process so disclosed.
[0103] Moreover, certain features that are described in the disclosure in the context of separate embodiments can also be implemented in combination in a single embodiment. Conversely, various features that are described in the context of a single embodiment can also be implemented in multiple embodiments separately or in any suitable subcombination. Furthermore, although features may be described above as acting in a particular combination, one or more features from a claimed combination may in some cases be deleted from the combination, and the combination may be claimed as a subcombination or variation of the subcombination.
[0104] Furthermore, although operations may be shown in the figures or described herein in a particular order, such operations need not be performed in the particular order shown, or in sequential order, or all of the operations to achieve the desired results. Other operations not shown or described may be incorporated into the exemplary methods and processes. For example, one or more additional operations may be performed before, after, simultaneously with, or between any of the described operations. Furthermore, operations may be rearranged or reordered in other implementations. Those skilled in the art will appreciate that in some embodiments, the actual steps taken in the illustrated and / or disclosed processes may differ from those shown in the figures. Depending on the embodiment, some of the steps described above may be removed and other steps may be added. Furthermore, the features and attributes of certain embodiments disclosed above may be combined in different ways to form additional embodiments, all of which are within the scope of the present disclosure. Also, it should be understood that the separation of various system components in the above-described embodiments should not be understood as requiring such separation in all embodiments, and that the components and systems described may generally be integrated into a single product or packaged into multiple products. For example, any of the components for the energy storage systems described herein can be provided separately or integrated (e.g., packaged together or attached together) to form an energy storage system.
[0105] For purposes of this disclosure, certain aspects, advantages, and novel features are described herein. Not necessarily all such advantages may be achieved in accordance with any particular embodiment. Thus, for example, one skilled in the art will recognize that the present disclosure may be embodied or performed in a manner that achieves one advantage or group of advantages as taught herein, without necessarily achieving other advantages as may be taught or suggested herein.
[0106] Conditional language such as "can," "could," "could," "may," and the like, unless otherwise indicated or understood otherwise within the context as used, is generally intended to convey that certain embodiments are included while other embodiments do not include certain features, elements, and / or steps. Thus, such conditional language is not generally intended to imply that features, elements, and / or steps are in any way required by one or more embodiments, or that one or more embodiments necessarily include logic for determining whether those features, elements, and / or steps are included in or should be performed in any particular embodiment, with or without user input or instruction.
[0107] Unless otherwise noted, conjunctions such as "at least one of X, Y, and Z" are understood apart from the context in which they are commonly used to convey that an item, term, etc. can be either X, Y, or Z, and thus such conjunctions are not intended to generally imply that a particular embodiment requires the presence of at least one of X, Y, and at least one of Z.
[0108] Language of degree, such as the terms "approximately," "about," "generally," and "substantially," refers to a value, amount, or characteristic that approaches a stated value, amount, or characteristic that still performs a desired function or achieves a desired result.
[0109] The scope of the present disclosure is not intended to be limited by the specific disclosure of preferred embodiments in this section or elsewhere herein, but may be defined by the claims, as presented in this section or elsewhere herein, or as presented in the future. The language of the claims is to be interpreted broadly based on the language used in the claims, and is not limited to the examples described in this specification or during the practice of this application, which examples are to be interpreted as non-exclusive.
[0110] Embodiment Various exemplary embodiments are provided below.
[0111] 1. A dry electrode film of an energy storage device comprising: a dry active material, the dry active material comprising a Group 14 active material and a graphite active material; and a dry binder, wherein the dry electrode film is self-supporting.
[0112] 2. The electrode film of embodiment 1, wherein the dry electrode film comprises about 1% to 30% by weight of a Group 14 active material.
[0113] 3. The electrode film of embodiment 2, wherein the dry electrode film comprises about 10% to 30% by weight of a Group 14 active material.
[0114] 4. The electrode film of any one of embodiments 1 to 3, wherein the Group 14 active material comprises at least one of silicon and tin.
[0115] 5. The electrode film of any one of embodiments 1 to 4, wherein the Group 14 active material is selected from at least one of pure silicon, silicon oxide (SiO), silicon-carbon composites, silicon alloys, and SiH.
[0116] 6. The electrode film of embodiment 5, wherein the silicon-carbon composite is selected from at least one of silicon graphene (SiC), tin graphene, silicon graphite (Si / C), tin graphite, silicon oxide graphene (SiOC) and silicon oxide graphite (SiO / C).
[0117] 7. The electrode film of embodiment 5, wherein the silicon alloy is selected from at least one of Si-Al and Si-Sn.
[0118] 8. The electrode film of any one of embodiments 1-7, wherein the Group 14 active material is prelithiated.
[0119] 9. The Group 14 active material has a D of about 1 μm to about 10 μm.50 9. The electrode film of any one of embodiments 1 to 8, comprising particles having a primary particle size.
[0120] 10. The electrode film of any one of embodiments 1 to 9, wherein the graphite active material is selected from at least one of artificial graphite and natural graphite.
[0121] 11. The electrode film of any one of embodiments 1 to 10, wherein the graphite active material comprises primary graphite (PG) particles and secondary graphite (SG) particles.
[0122] 12. The PG particles have a D of about 15 μm to about 30 μm. 50 12. The electrode film of embodiment 11 having a primary particle size.
[0123] 13.SG particles are about 2μm to about 10μm D 50 13. The electrode film of embodiment 11 or 12, having a secondary grain size.
[0124] 14. An electrode film according to any one of embodiments 11 to 13, wherein the mass ratio of PG particles to SG particles is 10:1 to 1:10.
[0125] 15. The electrode film of any one of embodiments 1 to 14, wherein the dry binder comprises at least one of carboxymethyl cellulose (CMC), poly(ethylene oxide) (PEO), polyacrylic acid, polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE).
[0126] 16. The electrode film of any one of embodiments 1 to 15, wherein the dry binder comprises a dry fibrillating binder.
[0127] 17. The dry electrode film of embodiment 16, wherein the dry fibrillating binder comprises polytetrafluoroethylene.
[0128] 18. An electrode comprising the dry electrode film according to any one of embodiments 1 to 17 in contact with a current collector.
[0129] 19. A lithium-ion battery comprising the electrode of embodiment 18.
[0130] 20. A method for manufacturing a dry electrode film for an energy storage device, comprising: mixing a dry Group 14 active material with a dry graphite material to form a dry active material mixture; mixing the dry active material mixture with a dry binder to form a dry electrode film mixture; and calendaring the dry electrode film mixture to form a free-standing dry electrode film.
[0131] 21. The method of embodiment 20, further comprising premixing the dry Group 14 active material with a first dry binder prior to mixing the dry Group 14 active material with the dry graphite material, and mixing the dry active material mixture with the dry binder comprises mixing the dry active material mixture with a second dry binder.
[0132] 22. The method of embodiment 21, wherein the first dry binder and the second dry binder are different binder materials.
[0133] 23. The method of any one of embodiments 20-22, wherein at least one of the premixing process, the first mixing process, and the second mixing process comprises a non-destructive mixing process.
[0134] 24. The method of embodiment 23, wherein the non-destructive mixing process comprises a resonant acoustic mixing process.
[0135] 25. The method of any one of embodiments 20-24, wherein at least one of the premixing process, the first mixing process, and the second mixing process comprises a high shear process.
[0136] 26. The method of embodiment 25, wherein the high shear process comprises jet milling.
[0137] 27. The method of any one of embodiments 20-26, wherein the dry graphite material comprises primary graphite (PG) particles and secondary graphite (SG) particles.
[0138] 28. PG particles have a D of about 15 μm to about 30 μm. 50 28. The method of embodiment 27, wherein the particle has a primary particle size.
[0139] 29.SG particles have a D of about 2 μm to about 10 μm. 50 The method of embodiment 27 or 28, wherein the particle size is a secondary particle size.
Claims
1. an active material including a Group 14 active material and a graphite active material; and a binder, wherein the electrode film is free-standing; the Group 14 active material comprises at least one of silicon and tin; the graphite active material comprises primary graphite (PG) particles and secondary graphite (SG) particles; the primary graphite (PG) particles have a D 50 average particle size of 15 μm to 30 μm; the secondary graphite (SG) particles have a D 50 average particle size of 2 μm to 10 μm; a mass ratio of the primary graphite (PG) particles to the secondary graphite (SG) particles is 10:1 to 1:10; the electrode film comprises 1% to 30% by weight of the Group 14 active material and is free of solvent residues; Electrode film for energy storage device.
2. 10. The electrode film of claim 1 , wherein the electrode film comprises 10% to 30% by weight of the Group 14 active material.
3. The Group 14 active material is pure silicon, silicon oxide (SiO x ), silicon-carbon composites, silicon alloys, SiH, tin, tin oxide, tin graphite, and tin graphene.
4. 4. The electrode film of claim 3, wherein the silicon-carbon composite material is selected from at least one of silicon graphene (SiC), silicon graphite (Si / C), silicon oxide graphene (SiOC), and silicon oxide graphite (SiO / C).
5. The electrode film of claim 3 , wherein the silicon alloy is selected from at least one of Si—Al and Si—Sn.
6. The electrode film of any one of claims 1 to 5, wherein the Group 14 active material is prelithiated.
7. The electrode film according to any one of claims 1 to 6, wherein the graphite active material is selected from at least one of artificial graphite and natural graphite.
8. The electrode film of any one of claims 1 to 7, wherein the binder comprises at least one of carboxymethyl cellulose (CMC), poly(ethylene oxide) (PEO), polyacrylic acid, polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE).
9. The electrode film of any one of claims 1 to 8, wherein the binder comprises a fibrillating binder.
10. The electrode film of claim 9 , wherein the fibrillating binder comprises polytetrafluoroethylene.
11. An electrode comprising the electrode film according to any one of claims 1 to 10 in contact with a current collector.
12. A lithium ion battery comprising the electrode of claim 11.
13. A method for manufacturing a dry electrode film for an energy storage device, comprising: a first mixing process including mixing a dry Group 14 active material with a dry graphite material to form a dry active material mixture; a second mixing process including mixing the dry active material mixture with a dry binder to form a dry electrode film mixture; and calendering the dry electrode film mixture to form a free-standing dry electrode film. the dry Group 14 active material comprises at least one of silicon and tin; the dry graphite material comprises primary graphite (PG) particles and secondary graphite (SG) particles; the primary graphite (PG) particles have a D 50 average particle size of 15 μm to 30 μm; the secondary graphite (SG) particles have a D 50 average particle size of 2 μm to 10 μm; a mass ratio of the primary graphite (PG) particles to the secondary graphite (SG) particles is 10:1 to 1:10; the dry electrode film comprises 1% to 30% by weight of the dry Group 14 active material; A method for manufacturing dry electrode films for energy storage devices.
14. 14. The method of claim 13, further comprising a pre-mixing process comprising mixing the dry Group 14 active material with a first dry binder prior to mixing the dry Group 14 active material with the dry graphite material, and mixing the dry active material mixture with the dry binder comprises mixing the dry active material mixture with a second dry binder.
15. The method of claim 14 , wherein the first dry binder and the second dry binder are different binder materials.
16. 16. The method of claim 14 or 15, wherein at least one of the pre-mixing process, the first mixing process, and the second mixing process comprises a non-destructive mixing process.
17. The method of claim 16 , wherein the non-destructive mixing process comprises a resonant acoustic mixing process.
18. The method of any one of claims 14 to 17, wherein at least one of the premixing process, the first mixing process, and the second mixing process comprises a high shear process.
19. 20. The method of claim 18, wherein the high shear process comprises a jet milling process.
20. The method according to any one of claims 13 to 19, wherein the method is a dry production method.
21. The electrode film of claim 1, wherein the secondary graphite (SG) particles are different from the primary graphite (PG) particles.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP1995235293A
Nonaqueous electrolyte secondary battery
JP1998270086A
Nonaqueous electrolyte secondary battery
JP2004327282A
Non aqueous electrolyte secondary battery
JP2006164960A
Non-aqueous electrolytic liquid battery
JP2007134108A